Uberisation risk of nursing work in times of Covid-19 pandemic: experience report (Research, Society and Development, 2020)
Objective: Describe the experience of hiring and working in nursing, in the context of care for patients with Covid-19, and to discuss ways of empowering nursing to cope and transform a work scenario that makes workers precarious. Method: This is an experience report, which took place in May and June 2020, in Rio de Janeiro, Brazil, which deals with working conditions and bonds in the service environment for people with Covid-19. Results: There was an extreme precariousness of nursing work, which points to a process of uberization of the profession. The professional's day-to-day availability for work (just-in-time worker) was observed; the responsibility to purchase their own personal protective equipment and the pay per hour worked. Final considerations: It concerns the combination of this precarious context with the pandemic scenario, since it enhances the illness of the nursing worker, lacking measures for coping and empowering nursing to transform this situation.